Comprehensive review of vibration-based analysis for wind turbine condition monitoring - Al-Hinai, Abdulhamid Hamdan; Varaprasad, Karu Clement; Kumar, V. Vinod (Universitas Muhammadiyah Magelang, 2024)
Wind energy production relies heavily on the efficiency of wind turbine systems. The routine condition monitoring and maintenance of these systems are necessary to maintain healthy operation, reduce maintenance costs, minimize downtime, and extend the lifespan. Vibration based analysis is an essential technique for wind turbine condition monitoring that enables early detection of mechanical faults, abnormal behavior and degradation mechanisms, and lessens the risk of unexpected failures. This review paper explores an intensive review of various vibration based techniques of condition monitoring, their advancements, challenges, and trends. This review paper reveals that this technique of condition monitoring is effective and essential to ensure the efficiency of wind energy systems. The review paper identifies future research prospects and potential technological advancements to ensure wind energy systems' reliability, safety, and optimal performance.